A new species of stone loach of the genus Mustura (Teleostei: Nemacheilidae) from Chindwin River drainage, Manipur, north-eastern India - Chinglemba, Yengkhom; Rameshori, Yumnam; Vishwanath, Waikhom (Zootaxa, 2021)
Mustura taretensis, a new nemacheilid loach, is described from the Taret River, a tributary of the Yu River, Chindwin River drainage, Manipur, India. The new species is distinguished from all its congeners by a unique combination of the following characters: body with 12–13 irregular dark-brown blotches or bars on flank, alternating with 11–16 irregular dark-brown saddles on the back; dorsum of head with a distinctly visible rhomboid dark-brown mark encircling a pale oval area on the nape; dorsal fin with 9½ or 10½ branched rays; lateral line complete; a well-developed free posterior chamber of air bladder, the halves of air bladder capsules connected by a manubrium; poorly developed processus dentiformis; suborbital flap present in males; and body depth 12.8–16.0 % SL. The generic status of Mustura chindwinensis, M. dikrongensis, M. tigrina and M. tuivaiensis are also discussed in the paper.